Kualitas Semen Segar Babi Berdasarkan Umur dan Ras di Kabupaten Kupang - Ardi, Maria Yosefina; Tophianong, Tarsisius C; Gaina, Cynthia D (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
The study aims to see how age and race affect the quality of fresh cement between pigs. The cement sources used in the study came from pigs of different ages of 9 months, 1.4 years, and 2.5 years. The pig races used were Landrace pigs and Duroc. Cemented is collected using the method of massage and then macroscopic and microscopic evaluation. The data from the cement evaluation will be a descriptive analysis presented in the form of the chart. Studies show 2.5-year-old pigs have a better fresh cement quality than a 9-month-old pig and 1.4 years old. The Landrace pig also has better fresh cement quality than the Duroc pigs.